A Longitudinal Analysis Of The Decision-Making Process Following The Palu Triple Disaster (2018-2025) - Munira Ramadhani; La Samudia Dalili (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This report provides a longitudinal analysis of decision-making processes in managing the earthquake, tsunami, and liquefaction disasters that struck Palu, Central Sulawesi, from 2018 to 2025. The combination of these disasters—particularly the unprecedented scale of liquefaction—positions Palu as a distinctive case study in crisis governance. The study traces the evolution of decision-making from the immediate aftermath of the disaster to the later phases of rehabilitation and reconstruction. In the emergency response phase, decisions were predominantly intuitive and reactive, shaped by the constraints of bounded rationality, limited information, and urgent life-saving priorities. As the situation transitioned into rehabilitation and reconstruction, the approach shifted toward more structured, analytical, and data-driven decision-making models. This transformation reflected the incorporation of lessons learned from early challenges, the integration of multi-stakeholder perspectives, and the adoption of systematic planning tools. The triple disaster also acted as a critical juncture that catalyzed structural reforms in policy, particularly in spatial planning and disaster risk reduction at both regional and national levels. Policy shifts included stricter zoning regulations, enhanced building standards, and the institutionalization of community-based disaster preparedness programs. Through its longitudinal perspective, the report examines key decisions taken during different phases, highlighting the interplay between political will, institutional capacity, and community resilience. It also identifies major implementation challenges, such as coordination gaps among agencies, resource limitations, and socio-cultural factors influencing local compliance. The analysis concludes with evidence-based policy recommendations aimed at strengthening future disaster governance. These include enhancing early warning systems, mainstreaming disaster risk reduction into development planning, improving inter-agency coordination, and fostering sustained community engagement. By capturing the dynamic nature of decision-making over time, this report contributes valuable insights for policymakers, practitioners, and scholars seeking to improve resilience in disaster-prone regions.